Journalistic articles - Bodden, Valerie (Mankato, MN : Creative Education, 2011)
"An introduction to the ways that writers compose newspaper and magazine stories. Excerpts and analysis help to explain the importance of structuring and accuracy in this nonfiction form"--Provided by publisher.
Includes bibliographical references (p. 47) and index.
Keywords: Feature writing -- Juvenile literature; Journalism -- Authorship -- Juvenile literature